Editorial Vol.1(1) - Kunwar, Ramesh Raj (Journal of APF Command and Staff College, 2018)
APF Command and Staff College is established to enhance the professionalism of mid-level officers of Armed Police Force, Nepal. The college is imparting empirical knowledge blending it with the practical aspects, so that officers will be able to cope with the emerging non-traditional security paradigms and other security concerns. Apart from its designed syllabus, College is also conducting seminars, conferences and workshops as part and parcel in cooperation and collaboration to Tribhuvan University and other academic institutions. College has published this noble journal to reflect its conceptual, theoretical and empirical research. The research has been confined to ethos of security, development and peace spectrum. It encompasses articles from scholars, researchers and practitioners aligning it with contemporary issues and security related dynamics of modern era. Professors, academics, researchers, policy makers and students may seize learning opportunity and will highly be benefited from the articles included in the journal. The editorial board reserves the right to edit, moderate or reject the article submitted. The articles included in this journal are mostly research based. Views expressed in the articles are purely personal and academic opinion of the authors and are not necessarily endorsed by APF Command and Staff College and editorial board.